In Vitro Wear Performance of X-ray Cross-Linked Vitamin E Blended Polyethylene. (March 2020) - Mulliez, M.A.; Fritz, B.; Holderied, M.; Schilling, C.; Grupp, T.M.
Abstract: The most common radiation cross-linking methods are electron-beam and Gamma-irradiation. Gamma-irradiation has a very low dose rate and e-beam serious penetration limitations. X-ray exhibits an excellent penetration capacity with a moderate dose rate. The objective of the study was the investigation of the wear behavior of vitamin E blended Ultrahigh Molecular Weight Polyethylene highly cross-linked by X-ray as an alternative cross-linking technology. We hypothesized that using same dose and irradiation temperature the wear behavior would be equivalent regardless of the radiation source. Hip wear simulation was performed with five different polyethylene acetabular inserts articulating with 40 mm diameter cobalt‑chromium heads. Two X-ray doses of 80 and 100 kGy and two irradiation temperatures each, i.e. room temperature and 100 °C, were considered. The reference was Vitelene®, a vitamin E stabilized polyethylene cross-linked by e-beam with 80 kGy at 100 °C. The inserts were subjected to artificial aging for 2 weeks prior to test. Increasing both the dose and the irradiation temperature led to an improved wear performance. X-ray showed the ability to improve the wear resistance of polyethylene in the same range as e-beam, as both are ionizing irradiation. Significance: Highly cross-linked polyethylene has been established and taken over 80–100% of polyethylene usage in Total Hip Arthroplasty [1–3 ]. The goal is to retain its mechanical properties, oxidative stability and superior wear resistance over time, which is crucial in order to reduce the incidence of periprosthetic osteolysis and increase the service time over the second implantation decade [4 ]. Vitamin E stabilized polyethylene has been successfully introduced showing very good results at 5 years [5–7 ]. X-ray irradiation stands out by its worthwhile characteristics like high penetration capacity and moderate dose rate which extend the treatment possibilities of polyethylene and the preservation of its properties in the long term. Highlights: Equivalent wear performance of vitamin E stabilized polyethylene cross-linked by X-ray and e-beam. Temperature during cross-linking had more impact than dose on the wear resistance. X-ray is worthwhile: uniform dose repartition, high penetration and moderate dose rate.